Estratégias para descompactação mecânica e biológica de latossolo vermelho no Sudoeste do Paraná - Haskel, Maiara Karini (2025)
After fifty years of adopting no-tillage (NT), due to the low species diversity and the addition of straw, the debate continues regarding the need for soil tillage practices to reduce compaction. Our objective was to evaluate equipment and intervals of soil preparation with the use of cover crops on soil physical attributes, organic matter, and plant performance. The study was conducted in the experimental area of UTFPR, Dois Vizinhos, Paraná, on a Latossolo vermelho, in an experiment initiated in 2015. The experiment consisted of a 5x4 factorial design, with five soil preparation systems: notillage (NT); no-tillage chiseled annually (PDEa); no-tillage chiseled with three-year intervals (PDEi); no-tillage with minimum practice chiseled annually (PDPMa); notillage with minimum practice chiseled every three years (PDPMi). The four cover crop treatments were: black oats; vetch; forage radish; and a triple consortium of these crops. After the cover crops, maize was planted, and during the off-season, starting in 2019, buckwheat was planted. The soil chiseling were carried out in May each year, following the scheduled interval. The thesis consists of two studies: 1) Soil physical parameters and corn productivity at different intensities of chiseled and use of cover crops; 2) Soil organic matter in areas with different intensities and preparation equipment and the use of cover crops. The physical parameters were determined in 2021, before and after soil preparation, in soil layers of 0.0-0.05, 0.05-0.10, 0.10-0.20, and 0.20-0.40 m, while soil organic matter was analyzed in 2018 and 2021 for the same soil layers. In addition to soil data, dry matter of plants and maize productivity were determined from 2015 to 2021. The data were subjected to analysis of variance, and the means were compared by the Skott Knott test. For all variables analyzed concerning physical attributes, no interaction was found between the preparation systems and cover crops; however, there were differences between the isolated factors. The most evident findings were for aggregate distribution after preparation, where a higher concentration of larger aggregates was found in the NT treatment or treatments with lower tillage intensity, and soil penetration resistance, which showed that after preparation, there was a reduction in values compared to NT, but considering the evaluation before preparation, it had a null effect after 12 months. The cover crops in succession to maize did not differ among themselves in terms of physical parameters and organic matter. Soil chiseling showed an immediate reduction in soil penetration resistance after preparations compared to NT, but NT did not show physical restriction based on the tested variables. For maize the tested cover crops and soil chiseled did not show changes in average productivity over the six years of study. However, the use of cover crops in succession to maize is considered ideal for increasing organic matter and reducing soil penetration resistance, since treatments with higher tillage intensity caused a reduction in the COT stock.